Experimental Study on the effect of Cooling Media on Impact Strength in the Heat Treatment Process of Medium Carbon Steel S45C - Risal, Syah; Mahadir, Mahadir; Suyuti, Muhammad Arsyad; Nur, Rusdi (INTEK: Jurnal Penelitian, 2022)
Steel possesses mechanical properties that can enhance the hardness and microstructure of its surface, and heat treatment is one way to achieve these properties. This study aimed to investigate the impact of different cooling media on the heat treatment process and the resulting impact strength of S45C medium carbon steel. The steel specimens were heated at various temperatures (800oC, 850oC, and 900oC) in a furnace and then cooled using three different media: water, oil, and air. The study concluded that for all three temperatures, the specimens cooled with oil had the highest impact value. Furthermore, oil and air immersion resulted in ductile fractures, while water immersion caused brittle fractures.